2020
DOI: 10.1016/j.ufug.2019.126501
|View full text |Cite
|
Sign up to set email alerts
|

Biocultural diversity (BCD) in European cities – Interactions between motivations, experiences and environment in public parks

Abstract: Biocultural diversity (BCD) in European cities-interactions between motivations, experiences and environment in public parks. Urban Forestry & Urban Greening, in press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Wang et al [8] and Liu et al [9] identified four main factors that influence the use of urban parks: socio-demographic factors, residential space characteristics, personal factors, and park characteristics. Relaxation, physical exercise, socializing, and playing with children have been identified as important motivating factors for park use [8][9][10][11][12][13]. Referrals from others may provide motivation too, and different information sources can have an impact on park usage [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [8] and Liu et al [9] identified four main factors that influence the use of urban parks: socio-demographic factors, residential space characteristics, personal factors, and park characteristics. Relaxation, physical exercise, socializing, and playing with children have been identified as important motivating factors for park use [8][9][10][11][12][13]. Referrals from others may provide motivation too, and different information sources can have an impact on park usage [14].…”
Section: Introductionmentioning
confidence: 99%
“…The main factors limiting the use of parks were time limitations and limited park access [9]. Previous studies in European cities reported that the primary motivation for visiting urban parks is to seek moral relaxation and a natural experience [12,15,16]. With additional facilities for activities in parks, visit frequency may increase [17].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to biodiversity may be encouraged or discouraged through aspects of the environmental/socio-cultural context, for example amenities (e.g. public toilets), park programming (Hunter, Cleary and Braubach, 2019;Vierikko et al, 2020), accessibility and maintenance status of the space where biodiversity is found, perceived safety in the space where biodiversity is, and other space-related variables such as size, type, land ownership (that can also be considered confounders) (Bratman et al, 2019). Individual characteristics, such as personal time demands, transport corridors, may also influence exposure (Bratman et al, 2019).…”
Section: Modifying Variablesmentioning
confidence: 99%
“…As McDonald et al rightly note, "Nature in and near cities is crucial not just for maintaining biodiversity but also for ensuring human wellbeing, which depends on the benefits that nature provides" (McDonald et al 2018, p. 9). Urban green spaces provide multiple benefits, and public parks in particular have a key role in supporting ecological and social sustainability in cities, contributing to human-nature interactions (Vierikko et al 2020). The parts of a city that support natural structures comprise the Urban Green Infrastructure (UGI) that links very directly to urban ecosystem services (Childers et al 2019).…”
Section: Urban Metabolism and The Impact Of Cities Beyond Their Bordersmentioning
confidence: 99%